If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x-4)-3x=9-6x
We move all terms to the left:
-2(x-4)-3x-(9-6x)=0
We add all the numbers together, and all the variables
-2(x-4)-3x-(-6x+9)=0
We add all the numbers together, and all the variables
-3x-2(x-4)-(-6x+9)=0
We multiply parentheses
-3x-2x-(-6x+9)+8=0
We get rid of parentheses
-3x-2x+6x-9+8=0
We add all the numbers together, and all the variables
x-1=0
We move all terms containing x to the left, all other terms to the right
x=1
| 9x-3=7x-23 | | 2-x^2=98 | | -3(x-4)-9=-2x+12 | | y=40(1-0.03)^10 | | 3-9x=23-7x | | -4(8-8a)=160 | | 6x+12=5x+4+x | | 6(5)+5y=35 | | 5(2n+1)=7(4n+4)+7 | | 9-3x=23-7x | | 3x-2=92 | | 7–6=n | | -9+5x-2x=3+x | | n+7=6 | | n–6=7 | | 4(x-3)-2x=2 | | 3^9x=475 | | -1/2x-7=7/5x-3/2 | | 79/18-32/18=n | | 4x-10=4x-2x+2 | | =24+18t | | (1+r)^10=1.25 | | (3x+13)=83+(x+10) | | 100000^x=2 | | 1/4+1/4x=1/2x-3 | | -4(5t-5)+8t=4t-9 | | 509=w+250 | | 5(4-4x)=20-x | | -8u+4(u-6)=8 | | 13x+7x=188 | | 8-2(2x-4)=-36 | | 9/1610=d/6.4 |